Impacts of climate change on water demand and duration forage sorghum and cowpea cycle in the state of Pernambuco - José Edson Florentino de Morais (Revista Brasileira de Geografia Física, 2015)
The increase in the occurrence of extreme weather events in recent decades is a strong evidence of climate change. In semiarid regions, where the pressure of desertification has intensified, are expected to decrease in the availability of water and higher occurrence of drought periods, and, consequently, effects on physiological response of plants. Thus, the objective of analyzing the impacts of climate change scenarios on the duration of phenological cycle and water demand of forage sorghum and cowpea, grown in the State of Pernambuco. Monthly values were used normal climatological solar brightness, air temperature, relative humidity and wind speed of ten municipalities. It was considered an increase of 1.8° C (B2 Scenario) and 4.0° C (A1F1 Scenario) on air temperature and a decrease of 5.0% of the absolute values of relative humidity, in addition to the 22% increase in stomatal resistance and 4% in leaf area index. Based on this information were generated three scenarios: current situation and future projections for B2, A1F1. The results revealed an average reduction of 11% (B2) and 20% (A1F1), and 10% (B2) and 17% (A1F1) for the duration of the cycle, and 4% (B2) and 8% (A1F1), and 2% (B2) and 5% (A1F1) in accumulated water demand for forage sorghum and cowpea, respectively. It is concluded that the magnitude of the reductions in the duration of the cycle and the simulated water demand for crops of forage sorghum and cowpea ranged space-temporarily in the State of Pernambuco with climate change scenarios.